Pelatihan Gitar bagi Mahasiswa STT JKI Salatiga - Yudi Novrian Komalig; Poedji Soesila; Paulus Dwi Hananto (Magistrorum et Scholarium: Jurnal Pengabdian Masyarakat, 2025)
Guitar Training for Students of STT JKI Salatiga is a guitar training conducted to equip students before they go to field practice at churches especially located in remote areas. Previously, students felt they lacked skills in accompanying worship services, so the services provided were felt to be incomplete. The method used there are 3 stages, namely design, implementation, and evaluation. At the design stage, a site survey was carried out to see the facilities and infrastructure as well as the students' initial abilities. Based on that, training materials are prepared according to the needs of students. The training was carried out for 16 weeks where each week consisted of 1 meeting from September to December 2022. The material provided consisted of 9 main topics, from lectures to practice playing the guitar. The evaluation was carried out by holding group music presentations to accompany the worship songs by the participants.